The star and the zoo - Woolley, Katie; Bentley, Joyce; Peden, Sarah (London: QED Publishing, 2018)
The animals are settling down for the night when a star falls from the sky into the zoo. Little Star is desperate to get back home, but who will help her? Exploring themes of kindness, friendship, teamwork and learning to work together, this fun and engaging story also includes comprehension activities and extra discussion topics, making it perfect for supporting learning at school. Featuring original stories, delightful characters and humorous illustrations, Reading Gems is a series designed to spark a love of reading. It is a supplementary reading programme that is graded into four levels to perfectly suit a child$1 (Bs reading ability from an emerging reader to a confident, independent reader. Parents and teachers can be reassured that children are reading books that support their ability, challenge their reading skills and encourage reading confidence with every word on the page.s
Kids